Disparities in access to quality surgical care for women in resource-constrained settings: Bottlenecks and the way forward - Waqar, Usama; Shaheer Ahmed; Hareem Rauf; Ayesha Nasir Hameed; Hina Inam (Journal of the Pakistan Medical Association, 2022)
Women seeking surgical care are burdened with gender disparities, particularly in resource-limited settings. Such disparities can lead to women often presenting late with advanced disease and poor prognoses. The current narrative review was planned to find evidence for gender disparities, their implications, challenges faced by women seeking surgical care, and strategies to address them. Potentiating from interplay between various societal, sociocultural, and economic barriers, the main challenges included inadequate autonomy, financial constraints, transport and referral issues, lack of experienced women surgeons, privacy concerns, surgeon distrust, and higher thresholds for seeking care. While research revealed these underlying causes, much work remains for governmental healthcare bodies, the international community, surgical leadership, policymakers, surgeons, and family members of patients to act on the highlighted issues. Continuous...